Experimental Validation of Single Phase Series Active Power Filter Using Fuzzy Control Technique - Abdallah Alla Ben Abdelkader; Othmane Abdelkhalek; Ahmed Allali; Abdelmalek Meftouhi; Toufik Toumi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The aim of this paper is illustrating and exposing the performance of a Series Active Power Filter (SAPF) with PI controller and Fuzzy controller within simulation and experimental validations. This performance is best manifested in compensating the sags and the swells voltages and in eliminating the harmonic voltage and regulate the terminal voltage of the load by injecting a voltage component in series with source voltage which is increased or decreased from the source voltage, hence, maintaining the load side waveforms as pure sinusoidal. The control method used in this work is not so complex and it is based on a phase locked loop (PLL) that is used to control the active filter. It is valid only in the phase system. The efficiency of the method I suggested is affirmed through simulation results by MATLAB\Simulink® and some prototypes experiments. These results shows the capability of the proposed prototypes